WRITING ASSESSMENT STRATEGIES OF ENGLISH TEACHERS IN JUNIOR HIGH SCHOOL - Roma July Venny BR Silalahi; Mia Audina Simbolon; Erikson Saragih (JALL (Journal of Applied Linguistics and Literacy), 2022)
Writing assessment strategies are strategies that combine theory and practice and are then used to assess students' writing abilities and potential. This study looks at how teachers employ strategies to help students learn English in the subject of writing. The teaching and learning process would not be complete without a teacher's strategy. How teachers are active and innovative in their studying and teaching so that students may readily accept the subject matter. This study aims to look into teaching options for junior high school students in First Supplementary English who need to improve their writing skills as a necessity for effective learning. This paper summarizes the findings of a study that looked into how English teachers teach writing skills to junior high school students taking writing tests. This study employs quantitative research to get replies and answers from a variety of teachers regarding writing assessment procedures. Ten English teachers from various schools were asked to respond to a series of questions. Data collection was carried out through the distribution of google form links as material for analyzing answers from several teachers.Keywords: Teaching Writing, Writing Assessment, Writing Strategy.